Break the rules! the six counter-conventional mindsets of entrepreneurs that can help anyone change the world - Mullins, John W. (Ascent Audio, 2023)
In Break the Rules!: The Six Counter-Conventional Mindsets of Entrepreneurs That Can Help Anyone Change the World, celebrated London Business School entrepreneurship professor, keynote speaker, and bestselling author Dr. John Mullins delivers an eye-opening and insightful exploration of what sets successful entrepreneurs apart from other business people and from those who fail to reach their goals. You'll discover a compelling argument that successful entrepreneurs exhibit one or more of the six break-the-rules mindsets revealed in this book. Each of these six mindsets can be learned, practiced, and built upon-by anyone, in any business setting large or small, old or new-to create thriving businesses that grow and prosper. Mullins draws on over two decades of research to show you how to do exactly that. You'll also find: explanations of why the six break-the-rules mindsets fly in the face of conventional business and business school wisdom; strategies for dealing with, skating around, or otherwise overcoming the daunting obstacles that stand in every innovator's way; ways to challenge assumptions and mitigate risk in order to take advantage of opportunities that present themselves along your entrepreneurial path; and steps you can take now to make one or more of these mindsets your own.
Online resource; title from title details screen (O'Reilly, viewed March 7, 2023)
Keywords: Entrepreneurship -- Psychological aspects; Problem solving; Attitude (Psychology); Organizational effectiveness; Entrepreneuriat; Aspect psychologique; Résolution de problème; Attitude (Psychologie); Efficacité organisationnelle; Entrepreneurship; Psychological aspects; Audiobooks; Livres audio